Sperm characterization of the endangered Amazonian fish Hypancistrus zebra: Basic knowledge for reproduction and conservation strategies - Caldas, Jôsie Schwartz; Godoy, Leandro Cesar (Animal Reproduction Science, 2019)
Hypancistrus zebra is an ornamental fish endemic to the Xingu River (Brazilian Amazon) and is critically endangered by the construction of a hydroelectric plant in its habitat and illegal fishing. In an attempt to create a germplasm bank for conservation purposes, in the present study there was characterization of H. zebra sperm for the first time and assessment of sperm quality throughout the year after successive stripping. Semen was collected four times during a year, and there was similar (P > 0.05) high quality for all values of sperm variables evaluated. Hypancistrus zebra sperm had an average motility rate of 88.60 ± 2.49% and membrane integrity rate of 87.93 ± 1.88%. There was a peculiar characteristic for the species, with an intermediate sperm vigor (3.00 ± 0.13) and a long duration of motility (14.72 ± 1.31 min) which is uncommon for freshwater fish. Semen had an overall mean of 79.13 ± 9.78% normal spermatozoa and 20.96 ± 9.76% of sperm cells with some morphological abnormalities. The most frequent morphological abnormalities were a degenerated head, an isolated head and a coiled flagellum. The collection of good quality semen throughout the year allows for the possible use of artificial reproduction techniques and cryopreservation for development of a germplasm bank that could contribute to successful conservation of this endangered Amazonian fish. © 2019 Elsevier B.V.
Keywords: Animals; Animals Dispersal; Endangered Species; Environmental Protection; Fish; Physiology; Reproduction; Animals Distribution; Animal; Conservation Of Natural Resources; Endangered Species; Fishes; Reproduction